NON-UNIONS AFTER FIXATION OF HUMERAL FRACTURES USING HACKETHAL'S BUNDLE NAILING TECHNIQUE - PETR OBRUBA; STEFAN RAMMELT; LUBOMIR KOPP; KAREL EDELMANN; JAKUB AVENARIUS (Acta Ortopédica Brasileira, 2016)
ABSTRACT Objective: The aim of the study was to identify factors contributing to the development of non-union after fixation of diaphyseal humeral fractures using Hackethal's intramedullary nailing technique. Methods: In the time period from 2001 to 2010 156 patients with diaphyseal humeral fractures were treated surgically using Hackethal's technique. Six of them (3.8%) developed non-union. This group included three women and two men aged 63-69 years and one woman aged 37 years. The following parameters of the patients were recorded: age, gender, comorbidities, substance abuse, mechanism of injury, fracture type and location according to the AO/ASIF classification, and the operative technique. Results: A non-union developed in six patients treated with Hackethal´s method (3.8%). Five of six non-unions (83%) were observed in patients in their sixties. In the subgroup of sexagenarians, non-union developed in 20.8% of surgically treated patients, as compared to 3.8 % in entire group. In the union group, fractures have been caused by high energy trauma in 52% of patients. In patients who developed non-union, high energy trauma caused 67% of fractures. With correct surgical technique the development of a non-union was observed in 0.7% of patients, with incorrect technique in 35.7% (p<0.001). Conclusion: Treatment of diaphyseal humeral fractures with Hackethal's intramedullary elastic bundle nailing resulted in an overall high union rate. Factors contributing to the development of non-union were extension of this method to AO type B3 and C fractures and technical imperfection during implantation. Level of Evidence III, Prospective, Case-Control Study.